The correlation between diesel soot chemical structure and reactivity. (May 2020) - Guo, Yi; Ristovski, Zoran; Graham, Elizabeth; Stevanovic, Svetlana; Verma, Puneet; Jafari, Mohammad; Miljevic, Branka; Brown, Richard
Abstract: Four types of fuels blended with diesel in scaling proportion were used in a diesel engine to generate 13 different soot samples. The samples were characterised for their thermal-induced oxidation process with DSC and TGA from which the mass loss during each of three phases and 6 critical temperatures was obtained per sample. With the same samples, soot chemical structure was characterised by Raman, XPS and TEM. This analysis provided information on different carbon chemical structures, O/C ratio on the sample surface, and nanostructure (fringe length and tortuosity). It was observed that generally for oxygenated fuel blends, the soot samples are more reactive, have more O functional groups on the carbon layer edge plane and have smaller polyaromatic layer size than reference diesel soots, while aromatic fuel blends show the opposite trends. However, the trend was not distinctive for all the samples analysed. Nevertheless, the two groups of data are highly correlated which implies that the chemical structure is the underlying reason dominating the soot reactivity. Specifically, the soot samples with more O functional groups and/or C–C bonds on the edge plane, are more reactive, they lose more mass at the lower temperature range and require lower temperature to initiate oxidation. Graphical abstract: Image 1